Preparing Mexican-Origin Community Health Advocates (Promotores) to Conduct SBIRT for Problem Drinking in the Emergency Room. (December 2018) - Ramos, Rebeca; Cherpitel, Cheryl J.; Alvarez, Jose; Beltran, Oscar; Woolard, Robert; Villalobos, Susana; Bernstein, Judith; Bernstein, Edward
Community health advocates (CHAs), known as Promotores in Spanish-speaking communities, are an important resource for the mobilization, empowerment, and the delivery of health education messages in Hispanic/Latino communities. This article focuses on understanding cultural, didactic, and logistical aspects of preparing CHAs to become competent to perform a Screening Brief Intervention and Referral to Treatment in the emergency room. The CHAs training emphasizes making connections with Mexican-origin young adults aged 18 to 30, and capitalizing on a teachable moment to effect change in alcohol consumption and negative outcomes associated with alcohol use. We outline a CHA recruitment, content/methods training, and the analysis of advantages and challenges presented by the delivery of an intervention by CHAs.